Decreased phase information transfer from the mPFC to the BLA: During exploratory behavior in CUMS rats - Cao, Qingying; Wang, Zihe; Bai, Wenwen; Liu, Tiaotiao; Zheng, Xuyuan (Frontiers in Neuroscience, 2023)
Depression is a mental disorder characterized by aberrant exploratory behavior. Environmental factors such as chronic stress are commonly used for rodent models of depression. The medial prefrontal cortex (mPFC) and basolateral amygdala (BLA) are crucial sites in chronic stress-induced depressive subjects. Abated amplitude information transmission from mPFC to BLA occur during exploration in depressive-like rats; however, the interaction of phase from mPFC to BLA remain unclear. Therefore, we employed chronic unpredictable mild stress (CUMS) to model depression in rats and acquired local field potentials (LFPs) via multi-electrodes implanted in mPFC and BLA while rats (control and CUMS group respectively) were freely exploring in open field. Rats subjected to CUMS showed a reduced exploratory behavior. We applied weighted phase lag index (WPLI) within mPFC-BLA in exploratory behavior to show a conspicuous elevated phase synchrony in theta-frequency (4-12Hz) than other frequency bands both in control and CUMS group. Moreover, phase transfer entropy (PTE) in theta-range from mPFC to BLA of two group rats (control and CUMS rats) was computed. The results exhibited PTE of CUMS was significantly decreased compared with the control group. These findings demonstrated that attenuated phase information transfer might restrain exploration in CUMS rats.